Endophytic and rhizospheric bacteria associated with Paspalum atratum and its potential for plant growth promotion with different phosphate sources - de Paula, Ailton Ferreira; Cruz, Felipe de Paula Nogueira; Dinato, Naiana Barbosa; de Andrade, Paulo Henrique Marques; de Moraes, Amanda Carolina Prado; Junior, Waldomiro Barioni; Bernardi, Alberto Carlos de Campos; Vigna, Bianca Baccili Zanotto; Fávero, Alessandra Pereira; Lacava, Paulo Teixeira (Frontiers in Plant Science, 2022)
The genus Paspalum belongs to the family Poaceae and has several species that are native to Brazil. The Paspalum Germplasm Bank (GB) of the Brazilian Agricultural Research Corporation comprises approximately 450 accessions from 50 species. Among these accessions, P. atratum (BGP 308) has economic potential for forage purposes. However, the endophytic and rhizospheric microbial communities within this accession and their ability to promote plant growth remain unknown. The present study aimed to isolate the endophytic and rhizospheric bacteria associated with P. atratum and to assess their potential for plant growth improvement, so-called plant growth-promoting bacteria (PGPB). For the in vitro tests, nitrogen-fixing bacteria (NFB) were tested in nitrogen-free semisolid culture medium, phosphate solubilization (PS) was tested in nutrient agar medium supplemented with insoluble phosphate, and indoleacetic acid (IAA) production was tested with L tryptophan as the precursor. Fifty-four bacterial isolates presented the potential for NFB, PS, and IAA. These isolates were identified by 16S rDNA sequencing. A total of 116 endophytic and rhizosphere bacteria were obtained from the isolation. In the in vitro tests, 43 (37.00%) of these isolates showed positive NFB, PS, and IAA results. Eight of these 43 isolates were evaluated in vivo in a greenhouse using P. atratum caryopsis. The pots were filled with soil prepared with soluble phosphate (triple granulated superphosphate), sedimentary phosphate (Arad phosphate rock concentrate), crystalline phosphate (Cajati phosphate rock concentrate) and one control without phosphate. Morphological descriptors were measured, and the aerial dry matter was subjected to bromatological and chemical determination. Data were analyzed using analysis of variance (ANOVA) and principal component analysis (PCA). In the in vivo test, the 105FCR (crystalline phosphate + Pseudomonas sp.), 109FSE (sedimentary phosphate + Bacillus sp.), and 110 FSE (sedimentary phosphate + Enterobacter sp.) treatments showed the best results for plant growth promotion. This work made it possible to determine the bacterial community associated with P. atratum (BGP308) and to obtain new potential plant growth-promoting strains.